Hubungan Karies Gigi Terhadap Kualitas Hidup Yang Terkait Dengan Kesehatanh Gigi Dan Mulut Pada Remaja Usia 12-14 Tahun Di SMP Negeri 2 Jumantono Kabupaten Karanganyar - Novita Rianti, Ari, Dwi Kurniawati, SKG., MPH, drg. Suyadi (2016)
Dental caries is dental hard tissue's disease that characterize by tissue damage starts from tooth surface lead into a pulp. The main caused of caries was Streptococcus mutans. The prevalence of active caries in adolescents aged 12 years was 43.4% and that have experienced caries by 67.2%. Dental caries was one of the factors that affect quality of life. This study aimed to determine the relationship of dental caries toward quality of life in adolescents aged 12-14 years. The research method was analytical observational with cross-sectional study have been held in SMP Negeri 2 Karanganyar Jumantono. The sample was 110 students aged 12-14 years selected using Simple Random Sampling. Data were analyzed using Spearman's correlation. The number of caries was used of odontogram and the depth of caries measured using a pre determined score, while instrument that used to measure quality of life related to oral health was OHIP (Oral Health Index Profile-14) questionnaires. The results showed that the quality of life are in great category by 58.2% and both depth of the superficial caries and the average number of caries was three. Spearman's test with R = -0, 519 and P = 0, 000, meaning that caries depth and quality of life with a negative correlation direction. The value of the number of caries in the table above were obtained value of R = -0, 127 and P = 0, 185, meaning there was no correlation or relationship between the number of caries toward quality of life. The results can be concluded that there was relationship between the depth of caries toward quality of life with a negative correlation direction where the higher caries the declining quality of life. Keywords: Dental Caries, Quality of Life, Adolescent